Pola Kemitraan dan Pendapatan Peternak di KPT Maju Sejahtera Kecamatan Tanjung Sari Kabupaten Lampung Selatan - Jazim, Fahriza Anjaya; Rufaidah, Erlina; Indriani, Yaktiworo (Universitas Galuh, 2025)
The objectives of this study are to: identify the patterns, mechanisms, rights and responsibilities, and evaluate the partnerships implemented by KPT Maju Sejahtera; analyze the income of both partner and non-partner cattle farmers; and examine the factors influencing cattle farmers decisions to engage in partnerships. The research location was chosen purposively, considering that KPT Maju Sejahtera has been implementing a partnership program since 2017 and that South Lampung District is one of the population centres or beef cattle areas in Lampung Province. About 66 participants were chosen at random to participate in the research as respondents. The months of January through February in 2024 were used for data collection. The analysis method used to answer the first purpose was descriptive qualitative analysis; farming business analysis was used to answer the second; and binary logistic regression analysis was used to answer the third. The results showed that KPT Maju Sejahtera and IACCB had formed an agribusiness operational cooperation patternship pattern. The evaluation results of the partnership established between IACCB and KPT Maju Sejahtera showed that the partnership was going well in accordance with the agreed cooperation agreement. The average income of partner and non-partner cattle farmers in Tanjung Sari District was IDR 23.233.363,64 per 2,82 heads and IDR 19.282.909,09 per 2,73 heads, respectively. Education level and initial capital for male and female cattle had a significantly positive effect, while the initial number of cattle had a significantly negative effect on the likelihood of farmers deciding to participate in partner with IACCB.